The Budget for 1335 (1919) of İstanbul Şehremaneti - Cem Çetin (Maliye Çalışmaları Dergisi)
The financial and administrative structure of the Ottoman Empire went through an important transformation process during the Tanzimat period. In this context, budgets and local governments came to the fore. Although a previous culture of recording income and expenses existed in the past, budgets were prepared in the western sense for the first time. Established in 1854, Şehremaneti began its adventure of responding to the local needs of its citizens; thus, budgets and local governments intersected as a consequence and became known as Şehremaneti Budgets. The period 1918–1919 was important as it was the first year of the occupation of Istanbul. The 1919 budget of the Şehremaneti, housedin the National Library, belongs to this period. In the study, the 1919 Şehremaneti budget is examined emphasizing the financial concerns of bureaucrats and efforts to prepare the budget by examining the understanding of financial allocation of the time. In addition, the social and economic structure of the armistice period capital in the context of income and expense items is discussed. The 1919 Şehremaneti budget reveals the effort to prepare a budget, which served as the legal basis for the services offered by the municipality, in a realistic, multidimensional, and argumentative manner. Unlike more common macro studies, this article is intended to contribute to economic historians working on the period in micro-analysis.